2006
DOI: 10.1192/pb.30.6.210
|View full text |Cite
|
Sign up to set email alerts
|

NICE guidance in schizophrenia: how generalisable are drug trials?

Abstract: Aims and MethodTo test the National Institute for Clinical Excellence (NICE) assertion that characteristics of participants in the majority of clinical drug trials in schizophrenia do not reflect clinical practice. In particular they were concerned about the relative exclusion of women, older adults and patients with comorbidity. The baseline characteristics of a sample of 600 patients with schizophrenia recruited to be as representative as possible of UK community practice were compared with those from one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Whether clinically significant selection bias occurs during recruitment to clinical trials is contentious. Although Burns (2006) reported that the basic demography of patients in a large naturalistic study was similar to that of a widely reported RCT, other authors have noted that the more chaotic patient who is difficult to manage will not be entered into a clinical trial as, even if they consent, they will undoubtedly drop out of follow-up (Lester & Wilson, 1999; Harrison-Read et al , 2002). Trials rarely report the number of patients considered or screened for a trial who are never included.…”
Section: Randomised Controlled Trialsmentioning
confidence: 93%
“…Whether clinically significant selection bias occurs during recruitment to clinical trials is contentious. Although Burns (2006) reported that the basic demography of patients in a large naturalistic study was similar to that of a widely reported RCT, other authors have noted that the more chaotic patient who is difficult to manage will not be entered into a clinical trial as, even if they consent, they will undoubtedly drop out of follow-up (Lester & Wilson, 1999; Harrison-Read et al , 2002). Trials rarely report the number of patients considered or screened for a trial who are never included.…”
Section: Randomised Controlled Trialsmentioning
confidence: 93%
“…However, this is achieved by purposive sampling rather than quantitative ranking against a specific measure such as socio‐economic deprivation. Patients’ demographic and illness characteristics are not that different from those routinely described in drug trials (8, 13) – young middle aged, an excess of males with illness histories of up to 20 years (14). They were, however, slightly less symptomatic than those routinely recruited into drug trials (e.g.…”
Section: Discussionmentioning
confidence: 99%